Development of Cooperative Script Model Mathematics Learning Devices with Realistic Mathematical Approach to Improve Mathematical Communication Ability for Grade VII Algebraic Materials - Himawan Himawan; Widowati Widowati; Kristanti Ambar Puspitasari (Budapest International Research and Critics University, 2022)
This research aims to: (1) obtain a valid mathematics learning tools model cooperative script with realistic mathematics approaches to improve mathematics communication skills; (2) a practical mathematics learning tools model cooperative script with realistic mathematics approaches to improve mathematics communication skills; (3) test the effectiveness of mathematics learning tools model cooperative script with realistic mathematics approaches to improve mathematics communication skills; The research consisted of two stages. The first stage is developing a learning device. The second stage is the implementation of learning using the learning device. The development of learning tolls in this study adapting development model proposed by Thiaragajan, Semmel, & Semmel includes define, design, develop, and disseminate. Disseminate not implemented in this study. The average value of the validation by the experts that developed the device is good. Individual mastery test results showed t calculate  7.3420296 > t table so it can exceed Minimum Criteria of Mastery Learning. Average test results the classical completeness showed z calculate  2,4495 is outside the reception area of H₀. So, it can be concluded mathematics learning model of cooperative script with realistic mathematical approaches to effectively help student achieve complete Minimum Criteria of Mastery Learning. The result test difference in average value of mathematical communication ability test showed t calculate  6.277818 > t table. This means that the average student mathematical communication ability test experimental class is better than the average test communication ability mathematical student control class. Being two different test results show the proportion of z calculate  2.30551 is outside the reception area H₀. So it can be concluded that the number of students with communication skills math test scores reached the limit of Minimum Criteria of Mastery Learning in the experimental class more than the number of students who reach the limit value Minimum Criteria of Mastery Learning completed in experimental class. Data were analyzed by SPSS 17 resulted in the regression equation Y ̂ = 51.652 + 6.019X₁ + 5.562X₂, It means each additional character variable independence (X₁) of the unit will add to the value of mathematical ability test (Y ̂) of 6.019. Average each additional variable of mathematical communication skills (X₂) of the unit will occur the value addition of mathematical communication ability test (Y ̂) of 5.561.